ANALISIS FRAMING PEMBERITAAN PROGRAM MAKAN BERGIZI DALAM MEDIA TIRTO.ID DAN TEMPO.CO - Budi Aditya; Michael Jibrael Rorong (SCIENTIA JOURNAL, 2025)
This study aims to determine how Tirto.id and Tempo.co frame the issue of the nutritious meal program and examine the extent to which news that has informative and educational value in educating the public regarding the importance of consuming nutritious food is conveyed through social media. To collect data in the study to be accurate in the study, researchers used several data collection techniques such as observation, interviews, questionnaires, and documentation. The results of this study that framing analysis is a very important tool in analyzing news presented by a media. In this study, researchers used the Robert N. Entman model which includes a very detailed and complete concept of Robert N. Entman's model. Framing analysis greatly influences public views on the nutritious meal program that was raised as news by online media Tirto.id and Tempo.co each have fulfilled the main requirements in framing a news raised from an issue. These elements include Define Problem, Diagnose Causes, Make Moral Judgment and finally Treatment Recommendation. As long as this program is running, the media continues to monitor and present the development of this program. In general, this program represents a major step for the government to implement comprehensively. However, obstacles encountered on the ground have made it quite difficult for all parties involved, ranging from the very large budget that must be controlled for efficient operation to technical issues such as the lack of equitable distribution, which has resulted in many regions not yet implementing this nutritious meal program. Keywords: News framing, nutritious meal, media, tirto.id, tempo.co